2001
DOI: 10.1017/s1041610201007591
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Aging, and Cognitive Performance in a Cohort of Japanese Americans Aged 65 and Older: The Kame Project

Abstract: Objective: To investigate the effects of light to moderate alcohol consumption on cognitive performance. Design and Setting: A cross-sectional analysis including older Japanese Americans in King County, WA, enrolled in the Kame Project, a population-based study of cognition, dementia, and aging. Participants: 1,836 cognitively intact participants aged 65 and older who participated in the baseline (1992-1994) examination. Measurement: Cognitive performance was measured using the Cognitive Abilities Screening In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…The Whitehall II Study of middle-aged 1,761 women and 4,272 men found that moderate alcohol intake, compared to light intake, was associated with less risk for poorer overall cognition [6] . Others [1][2][3]28] , but not all [29] , have reported concordant results.…”
Section: Association Between Alcohol Intake and Globalmentioning
confidence: 84%
“…The Whitehall II Study of middle-aged 1,761 women and 4,272 men found that moderate alcohol intake, compared to light intake, was associated with less risk for poorer overall cognition [6] . Others [1][2][3]28] , but not all [29] , have reported concordant results.…”
Section: Association Between Alcohol Intake and Globalmentioning
confidence: 84%
“…For example, higher educational levels (Farmer et al, 1994;Lyketsos et al, 1999;Wight et al, 2002) and moderate alcohol consumption (Bond et al, 2001;Britton et al, 2004) have been previously shown to predict improved cognitive performance, whilst depressive symptomology (Wilson et al, 2002;Wilson et al, 2004), co-morbidities (Fillit et al, 2002;Rosano et al, 2005) and smoking (Kalmijn et al, 2002;Reitz et al, 2005) are associated with poorer cognitive performance. Although our choice of predictors was based largely upon the existent literature, we cannot exclude the possibility that some of our findings may be due to unmeasured factors and/ or residual confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have now reported that alcohol abstainers have lower scores on cognitive tests compared with moderate drinkers [31,[39][40][41][42] . This effect has occurred on measures of a range of cognitive abilities including processing speed, memory, verbal ability, visuospatial ability and reasoning, in samples of young [34,43] , middle [39] and older adults [42] , and across gender.…”
Section: Nonlinear Relationshipsmentioning
confidence: 99%